Malawi: Ending hunger and undernutrition: challenges and opportunities - Compact2025 (International Food Policy Research Institute, 2017)
This scoping report was prepared to inform the Compact2025 roundtable discussion by providing an overview of the food security and nutrition challenges and opportunities in Malawi. It reviews the food security and nutrition policy landscape across key sectors and actors in Malawi as well as critical knowledge, policy, and implementation gaps. It also assesses vulnerabilities to recurrent economic and climatic shocks such as those brought on by El Niño. Additionally, the scoping report presents a SWOT analysis (strengths, weaknesses, opportunities, and threats) that crystallizes the main elements that drive or hamper food security and nutrition in the country. To determine what is holding back progress, this study identifies several key research, policy, and action gaps, including the current disconnect between agriculture, nutrition, and health, and the need to put into action the policies needed to guide activities.